Correlation Analysis of the Carboxyl and Carbonyl Groups of Natural Organic Matter and the Formation Potential of Trihalomethanes and Chloral Hydrate - Xinwei Zhu; Minghua Li; Pengwei Yan; Jimin Shen; Jing Kang; Zhonglin Chen (Molecules, 2022)
Natural organic matter (NOM) has always been considered the main precursor of disinfection by-products (DBPs) during the chlorine disinfection of drinking water. This research focuses on investigating the correlation between the functional group (carboxyl and carbonyl groups) content of NOM and the formation of trichloromethane (TCM) and chloral hydrate (CH). The quantitative determination of carboxyl groups, carbonyl groups, TCM, and CH were conducted during the drinking water treatment processes with different coagulant dosages and with/without pre-oxidation by KMnO4 or NaClO. The most appropriate coagulant for the removal of conventional components was polyaluminum chloride (PAC), and the dosage was 110 mg/L. Up to 43.7% and 14.5% of the carboxyl and carbonyl groups, respectively, were removed through the coagulation and sedimentation processes, which can be enhanced by increasing PAC dosage. The filtration process further increased the removal rates of these two functional groups to 59.8% and 33.5%, respectively. The formation potential of the TCM and CH decreased as the PAC dosage increased. Pre-oxidation by KMnO4 (0.8–1.0 mg/L) effectively controlled the formation of DBPs while increasing the carboxyl and carbonyl group content. Pre-oxidation by NaClO decreased the formation of TCM rather than CH, and a suitable amount (0.5–1.0 mg/L) decreased the carboxyl and carbonyl groups. It was found that there was a good linear correlation between carboxyl groups and TCM and CH. The linear fit R2 values of the carboxyl groups to TCM and CH were 0.6644 and 0.7957, respectively. The linear fit R2 values of the carbonyl groups to TCM and CH were 0.5373 and 0.7595, respectively.